The impact of physical exercise on mental health and the relationship among physical exercise, emotional regulation and suicidal ideation in Chinese medical students - Zhang, Yiqi; He, Junlin; Ruan, Han; Yao, Pin; Ma, Guoliang (Frontiers in Psychology, 2025)
BackgroundThis study aims to investigate the mediating role of emotional regulation in the relationship between physical exercise and suicidal ideation among Chinese medical students. The study specifically examined how exercise-induced enhancement of emotional regulatory capacity may mitigate suicide risk through neurobiological and psychological pathways.MethodsA cross-sectional study assessed 852 medical students using the Physical Activity Rating Scale-3 (PARS-3) to categorize exercise intensity (low: 51.9%; moderate: 25.9%; high: 22.2%). Suicidal ideation was measured with the Positive and Negative Suicide Ideation Scale (PANSI), emotional regulation capacity with the Emotion Regulation Questionnaire (ERQ), and psychological symptoms with the Symptom Checklist-90 (SCL-90). Independent t-tests, ANOVA tests, and mediation modeling were used for analysis.ResultsThe prevalence of suicidal ideation was 8.10% (69/852), consistent with national epidemiological data. Males exhibited significantly lower depression (Δ = −1.24, p < 0.05) and anxiety (Δ = −0.87, p < 0.05) scores than females. Students engaging in high/moderate-intensity exercise demonstrated lower rates of depression and psychosis compared to low-intensity exercisers (p < 0.05). Emotional regulation mediated 38.1% of the protective effect of exercise against suicidal ideation (p < 0.01), aligning with established neurobiological pathways linking physical activity to mood regulation.ConclusionThe physical exercise habits of medical students are intricately linked to their mental and emotional well-being. It is recommended that medical institutions intensify efforts to promote physical exercise and encourage greater participation among medical students. This proactive approach can contribute to reducing suicidal ideation among medical students and enhancing their overall mental health.